Kierunki wykorzystania systemu jednorodnych grup pacjentów w zakładach opieki zdrowotnej - Macuda, Małgorzata (Ways of using DRG system in health care units, 2008)
Andrzej Sośnierz, the president of the National Health Fund, announced the implementation of diagnostic related groups in funded hospitals in Poland at the end of 2007. This system, already operating in many European countries (France, the UK, Italy, Spain, Germany and Switzerland), is based on DRG concept founded in the US A in the 70s. Besides being a tool of contracting and financing hospitals, it may also be used in some other ways in health care units. The DRG system characterizes the treatment process in a detailed way, both in a clinical dimension and costs, which creates common language between medical staff and administrative-economic staff. It can also be used as a statistical tool while planning possible medical services in a health care unit and as a tool of planning and controlling costs of those services.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 271-277